ความสัมพันธ์ระหว่างการสนับสนุนทางสังคมกับพฤติกรรมการใช้ แอพพลิเคชั่นไลน์ของผู้สูงอายุในจังหวัดอุบลราชธานี - Payungwong, Thitiporn; Sasithanakornkaew, Saranthorn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
This research had objectives: to compare demographic data of the behavior of elderly Line application users and to study the relationships between the emotional, physical, and societal social supports with elderly behaviors of LINE application users in Mueang District of Ubon Ratchathani province. The sample of this study were 400 respondents who are aged above 60, live in Mueang District of Ubon Ratchathani Province, and have used LINE application not less than 1 year. The study was quantitative research, and the research instrument used was a questionnaire for collection of the relevant data, and data was analyzed by statistics, namely, percentage, mean, t-test, one-way anova, and Pearson correlation coefficient. The research results found that the elderly who have emotional support is overall in the “high” level and the elderly who have physical and societal social support overall fall into the “medium” level. And, the demographic differences as the following: age, living area, occupation, education, income and inhibition of LINE application users were statistically significant at level .05, and the emotional, physical, and societal social support variables were associated with behaviors and characteristics of elderly users using LINE application statistically positive significant at level .01.